2014
DOI: 10.1088/1468-6996/15/1/015008
|View full text |Cite
|
Sign up to set email alerts
|

Atomic force microscopy visualization of hard segment alignment in stretched polyurethane nanofibers prepared by electrospinning

Abstract: Molecular-level orientation within nanofibers has been attracting attention as a tool for controlling and designing highly functional nanofibers. In this study, we used atomic force microscopy to visualize the phase separation between soft and hard segments on a polyurethane (PU) nanofiber surface prepared by electrospinning. Furthermore, the stretched nanofibers prepared with a high-speed rotating collector were found to have a different phase distribution in the phase-separated structure, with the hard segme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 29 publications
0
13
0
Order By: Relevance
“…The structure of microphase‐separated PUs can be easily investigated by AFM and usually, bright and dark regions in a phase‐contrast image are an indicator of changing surface properties . Hard segments generally appear as bright areas, while soft segments are anticipated to give dark contrast in the phase imaging . Phase‐contrast in AFM images for dry samples are given in Figure .…”
Section: Resultsmentioning
confidence: 99%
“…The structure of microphase‐separated PUs can be easily investigated by AFM and usually, bright and dark regions in a phase‐contrast image are an indicator of changing surface properties . Hard segments generally appear as bright areas, while soft segments are anticipated to give dark contrast in the phase imaging . Phase‐contrast in AFM images for dry samples are given in Figure .…”
Section: Resultsmentioning
confidence: 99%
“…Lee et al reported that the crystalline structure in fibers can be developed in ductile polymers. Polymers that have low T g values such as our novel PCPU ( T g = −22.9°C) take a longer time to crystallize . Overall, the sharper reflections in electrospun samples indicate that crystallization occurs during the electrospinning process when the polymer fibers are elongating and possibly after the fibers have dried and solidified.…”
Section: Resultsmentioning
confidence: 90%
“…The authors proposed that the strength and elastic modulus of the fibers are influenced by the crystal lamellar and amorphous fractions of the chains within the polymer fibers. Additionally, they proposed that structural formation changes taking place in the fibers during electrospinning, specifically crystallinity and molecular orientation impart physical uniqueness to the material and play an important role in the deformation behavior of the fibers . Strain to break values in the electrospun samples is somewhat lower than that of neat PCPU.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Polyurethanes are known to exhibit microphase separation of their flexible soft segments and rigid hard segments . The Oil‐Thickener PU microstructure alteration in the presence of hydrophobic SFO molecules was studied using AFM, anticipating a correlation to the network formation of Oil‐Thickener PU in SFO.…”
Section: Resultsmentioning
confidence: 99%